1994
DOI: 10.1093/ajcp/101.6.719
|View full text |Cite
|
Sign up to set email alerts
|

Use of Discriminant Analysis to Assess Disease Activity in Pulmonary Tuberculosis with a Panel of Specific and Nonspecific Serum Markers

Abstract: Several cell activation markers, acute phase reactants, enzymes, and antituberculous antibody serum levels have been proposed as possible markers to monitor disease activity in patients with tuberculosis. They have all shown limited sensitivity or specificity. The authors therefore attempted to generate a canonical variable using discriminant analysis, including sensitive and specific parameters, to be a reliable marker in classifying patients correctly during the course of pulmonary tuberculosis. The followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…However, this does not use information available in the quantitative data. This can be ameliorated by using the discriminant analysis, which represents one of the best methods of combining the discriminant power of more variables to obtain the most accurate classification between two or more groups (Ameglio et al, 1991(Ameglio et al, , 1994.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not use information available in the quantitative data. This can be ameliorated by using the discriminant analysis, which represents one of the best methods of combining the discriminant power of more variables to obtain the most accurate classification between two or more groups (Ameglio et al, 1991(Ameglio et al, , 1994.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology is currently applied in taxonomy. Several examples of the use of this method are also reported in the literature concerning different fields [14][15][16][17]20]. Recently, serum tumour marker levels were reliably used to distinguish between primary and metastatic malignant bone tumours [16].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, BOTHAMLEY et al [29] have found that the combined use of tests with antigens, such as p38, p19, p14, and LAM, and with monoclonal antibodies against them may considerably improve diagnostic sensitivity (up to 72%) compared to the single tests with LAM (32%) and with p19 (58%). VERBON et al [26] have obtained similar results with antigens of 10,16,24,30,38 and 70 kDa and the monoclonal antibody TB72 (specific for the p38 protein [15]). They have shown that test combinations, such as with the 10, 16, 24 kDa antigens and the antibody TB72, could improve the diagnostic sensitivity of each test.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, the test distinguished PPD-positive patients with bacterial pneumonia presenting with a clinical picture raising the suspicion of TB. The observation that MS2-34 is specific for active TB, and it is not recognized by IgG antibodies from patients with cured or inactive disease is quite interesting, since discrimination of active from inactive patients requires many immunological markers [30]. However, the sensitivity of the MS2-34/p38 IgM test is as high as that of the MS2-34/p38 IgG test.…”
Section: Discussionmentioning
confidence: 99%